First-principles study of adsorption, dissociation, and diffusion of hydrogen on α-U (110) surface - Zihan Xu; Chenglong Qin; Yushu Yu; Gang Jiang; Liang Zhao (AIP Advances, 2024)
According to the equilibrium crystal shape of α-U, the surface of α-U (110) is more stable and has a larger area fraction than α-U (001). Therefore, the adsorption, dissociation, and diffusion behaviors of H atoms and H2 molecules on the α-U (110) surface were systematically studied by first-principles calculations. The results show that there are only two stable adsorption sites for the H atom: the surface short-bridge site (SB1) and the subsurface short-bridge site (SB2). The adsorption of H2 molecules is divided into chemical adsorption of dissociated H2 molecules and physical adsorption of undissociated H2 molecules, and the LB2-ParL adsorption configuration is the most stable adsorption configuration for H2 molecule adsorption, with an adsorption energy of −0.250 eV. The work function and charge transfer show that adsorption of the H atom or H2 molecule leads to an increase in the work function value of the α-U (110) surface, which enhances the electronic stability of the α-U (110) surface. The projected density of states shows that when the H atom or H2 molecule is close to the α-U (110) surface, the 1s orbital electrons of the H atom will hybridize with the 5f/6d orbital electrons of the nearby surface and subsurface U atoms, and new hybridized orbital peaks appear near the −4.5 eV or −7.3 eV energy level. The climbing image nudged elastic band study shows that the surface free H atoms are very easy to diffuse between the surface short-bridge sites and the subsurface short-bridge sites but the diffusion between the short-bridge site and the triangular center site is extremely difficult.